2011
DOI: 10.1016/j.neurobiolaging.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine and CX3CR1 regulate hippocampal neurogenesis in adult and aged rats

Abstract: Microglia have neuroprotective capacities, yet chronic activation can promote neurotoxic inflammation. Neuronal fractalkine (FKN), acting on CX3CR1, has been shown to suppress excessive microglia activation. We found that disruption in FKN/ CX3CR1 signaling in young adult rodents decreased survival and proliferation of neural progenitor cells through IL-1β. Aged rats were found to have decreased levels of hippocampal FKN protein; moreover, interruption of CX3CR1 function in these animals did not affect neuroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
302
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(321 citation statements)
references
References 47 publications
16
302
2
1
Order By: Relevance
“…In line with Bachstetter et al (2011), we confirmed reduced hippocampal neurogenesis in 2-month-old KO mice. An ϳ25% decrease in the density of BrdU pos cells ( p ϭ 0.032) (Fig.…”
Section: Is Cx3cl1 Involved In Regulating Microglia-dependent Precurssupporting
confidence: 84%
See 2 more Smart Citations
“…In line with Bachstetter et al (2011), we confirmed reduced hippocampal neurogenesis in 2-month-old KO mice. An ϳ25% decrease in the density of BrdU pos cells ( p ϭ 0.032) (Fig.…”
Section: Is Cx3cl1 Involved In Regulating Microglia-dependent Precurssupporting
confidence: 84%
“…Experimental mice received 5 g of ␣-CX 3 CR1 (Torrey Pines Biolabs; n ϭ 8) (Bachstetter et al, 2011) or control IgG (Sigma-Aldrich; n ϭ 6 animals) per day (flow rate of 0.11 l/h) over a 2 week period, during which time the animals had access to a running wheel. After completion of the infusion period, the mice were killed, hippocampi were dissected, and cell preparations from two animals were pooled for each experimental repeat.…”
Section: Intraparenchymal Infusion Of CX 3 Cr1 Blocking Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have shown that this relates to activated microglia, supporting the anti-inflammatory fractalkine-CX3CR1 signaling has been shown to regulate neurogenesis, with exogenous fractalkine being able action of hUCBCs (70,71). As well as changes in microglia, the peripheral number of lymphocytes was into restore the age-related decrease in neurogenesis observed in aged rats (6). Modification of this signaling creased, whereas neutrophils were decreased in mice given the optimal dose, suggesting that the "immune depathway has also been shown in APP transgenic mice (23) and in AD patients (55).…”
Section: Introductionmentioning
confidence: 96%
“…A significantly reduced number of microglia was detected (3,7,42). However, there is an age-related loss of fractalkine, meaning that microglia are more likely to become in mice treated with the optimal number of hUCBCs compared with untreated mice and those given a differactivated with time and this could become excessive and eventually cause neural damage (6). In addition, the ent dose.…”
Section: Introductionmentioning
confidence: 99%